Use of Students’ Learning Outcomes as a Tool for Changing Teaching Content and Methodology: Assessment of Impact - Syed Shariq Naeem; Vandana Roy (MAMC Journal of Medical Sciences, 2022)
Objectives: Assessment of student’s learning outcomes in alignment with the teaching goals can be a tool for modification of curriculum and teaching methods. This study was conducted to evaluate the impact of a pharmacology curriculum on students’ learning outcomes and the use of their assessment as a tool for making curriculum changes. Materials and methods: An assessment of the students’ (exiting 2014) knowledge and skills at the end of their fifth semester training in pharmacology was carried out using a questionnaire that was developed to accommodate testing of all areas which are underlined in the Medical Council of India’s goals and objectives of teaching pharmacology to MBBS undergraduates at the time of designing of the study. Areas where lesser than 50% students scored well were identified for educational interventions with the next two batches of students (2015, batch B and 2016, batch C), who were then subjected to the same assessment. Results: Based on the learning outcomes, 15 areas were identified for educational interventions with batch 2015. Improvement in learning outcomes of students was observed in 10, ranging from 10% to 15% in batch 2015, whereas in batch 2016, an improvement of 20% was observed in three questions and >10% was observed in six questions. Overall improvement in the intervention questions was 60% (+9 questions) in batch 2015 and 80% (+12 questions) in batch 2016 when compared with preintervention batch 2014. The preintervention batch 2014 scored better overall than the intervention batches 2015 and 2016. Conclusions: Changing teaching content and method, based on assessment of students’ learning outcomes alone, may not translate into an improvement in students’ learning outcomes. Teachers must look for other factors that can impact students’ learning.